Measurement Matters: Family Leave Policies and Women's Employment - Brigid Cotter (Luxembourg Income Study (LIS), 2023)
Although work-family scholars generally agree that maternal and parental leave policies affect women's labor force outcomes, the direction and extent of this effect is highly contentious. Complicating the debate, parental leave policies are measured in a variety of ways in crossnational research, making it difficult to compare findings across studies. There is little assessment of how measurement affects outcomes or of alternate ways to measure these leave schemes. Using data from the Luxembourg Income Study (~2013) and an original collection of parental leave measures from 26 countries, this paper analyzes how different measurement strategies affect women's employment rates by examining combinations of paid and unpaid maternal and parental leave, wage replacement rates, job protection, and eligibility requirements. The results suggest that competing findings in previous work may be explained by scholars' focus on different pieces of maternal and parental leave policy, shedding new light on the importance of using comparable indicators. I argue for the use of reliable ways to measure policy, such as the importance of including wage replacement rates in future models for more consistent, complete perspectives of policy effect.
Keywords: 330; family policy; measuerment; labor market outcomes; employment; women